DINAMIKA KEBERADAAN TRANSPORTASI BEMO DI KOTA PADANG - -, Rahmiati - (Pendidikan Sosiologi, 2014)
been used for 52 years, but also has been survived from other transportations and government policy change in Padang city. The problems are formulated : how is the dynamic of existence transportasi in Padang, how is the relationship with the bemo driver IKABE and how is the influence of government policy toward bemo base station. The purpose of the research are to describe and analyze the dynamic of existence transportasi bemo in Padang, the relationship between the drivers and the influence of government policy toward bemo base station in Padang.This research is performed for 2 months, on July and August 2014. The analysis in this research uses analysis interactive. The approach of this research is qualitative descriptive analysis, which is done by 16 informant by using purposive sampling technique. It means informant selection based on certain criteria. The methods used for data collection are observation, indepth interview and document study.From the real results of the research we can summarize that the dynamics of transportation bemo in the Padang City. The beginning of its presence gave rise to attitudes of pros and cons, as seen from the pros it is communities who use the services of the bemo while the cons were from hansom carriage. Then if viewed from a number of routes, fares, and these often have a bemo base good changes that impact the development nor retrogression. And then a bemo has organization called the IKABE which was formed on January 3, 1967 and membership system this is the original IKABE to become a citizen of the Republic of Indonesia are engaged in the public transport system as well as ownership is individuals bemo. Next to the age of the older the bemo then Government undertook the rejuvenation of a bemo for 3 times: in 2003, 2005 and 2007. Last seen in terms of the relationships between drivers and bemo IKABE he became the relationship among them, cooperation, then it has the rights and obligations which must be accepted in a bemo driver pay in the IKABE organization and they have various forms of events and activities with in the organization such as payroll activities IKABE and form groups and events commemorating the arisan holidays of Islam. The next influence government policy against viewing the transfer base bemo is giving effect to the bemo driver and passenger revenue itself.